Intermedin A, a New Labdane Diterpene Isolated from Alpinia intermedia, Prolonged the Survival Time of P-388D1 Tumor-Bearing CDF1 Mice - Chen, Lih-Geeng; Su, Pei-Jung; Tsai, Po-Wei; Yang, Ling-Ling; Wang, Ching-Chiung (Planta Medica, 2017)
Eight ethanolic extracts of indigenous Taiwanese plants of the genus Alpinia were tested for tumor cytotoxicity against AGS, Hep G2, HeLa, KB, and HL-60 cells. Among the 50 % and 95 % EtOH extracts of eight Alpinia species, the cytotoxic effects of Alpinia intermedia leaves were the strongest. When the leaf extract of A. intermedia was partitioned using n-hexane and aqueous solvents, the n-hexane layer showed a greater cytotoxic effect and could prolong the survival time of P-388D1 tumor-bearing CDF1 mice. Two new labdane diterpene derivatives, intermedin A (1) and intermedin B (2), and coronarin E (3) were isolated from the n-hexane layer of A. intermedia. Intermedin A induced apoptosis in HL-60 cells at 30 µg/mL and significantly prolonged the survival time of P-388D1 tumor-bearing CDF1 mice by 48.7 % at 20 mg/kg of body weight. We suggest that intermedin A is a major compound of A. intermedia and has a cytotoxic effect on HL-60 and P-388D1 cells.
Keywords: Alpinia intermedia; Zingiberaceae; intermedin A; apoptosis; P-388D1 tumor-bearing CDF1 mice